Prenatal ontogeny of lymphocyte subpopulations in pigs - Sinkora, M; Sinkora, J; Reháková, Z; Splíchal, I; Yang, H; Parkhouse, R M; Trebichavsk, I (Immunology, 1998)
Although porcine lymphocytes have been classified into numerous subpopulations in postnatal animals, little is known about the ontogeny of these complex cell subsets. Using double- and triple-colour flow cytometry (FCM), we investigated the surface phenotype of fetal lymphoid cells in the thymus, cord blood, spleen and mesenteric lymph nodes at different stages of gestation. It was found that the major lymphocyte subpopulations started to appear at the beginning of the second third of the gestation period, with B cells being the earliest lymphocyte subpopulation to appear in the periphery. The T-cell receptor (TCR) gamma delta+ cells were the earliest detectable T-cell subset, developing first in the thymus and subsequently arriving in the periphery. Later in ontogeny, however, the number of TCRalpha beta+ lymphocytes rapidly increased, becoming the predominant T cells both in the thymus and in the periphery. Cells with the phenotype of adult natural killer cells were also identified in pig fetuses, though their nature and functional roles remain to be investigated. In addition, CD2 was expressed on most B cells whilst very few CD4+ TCRalpha beta+ cells or CD2+ TCRgamma delta+ cells expressed CD8, suggesting that the expression of CD2 and CD8 may reflect the functional status of the cells in postnatal animals. Taken together, this study has provided a systematic analysis of fetal porcine lymphocyte subpopulations and may provide the base for studies to establish the physiological roles of these lymphocyte subsets.
Keywords: podskupiny lymfocytů; Swine, Miniature; T-Lymphocytes; průtoková cytometrie; Receptors, Antigen, T-Cell, gamma-delta; Killer Cells, Natural; Gestational Age; plod; T-lymfocyty; receptory antigenů T-buněk gama-delta; Lymphocyte Subsets; Lymph Nodes; miniaturní prasata; slezina; Flow Cytometry; gestační stáří; Swine; B-lymfocyty; zvířata; B-Lymphocytes; lymfatické uzliny; Thymus Gland; prasata; Fetus; buňky NK; receptory antigenů T-buněk alfa-beta; thymus; Receptors, Antigen, T-Cell, alpha-beta; Spleen; Animals